2020
DOI: 10.1097/md.0000000000023544
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors for the postoperative pulmonary infection in patients with hypertensive cerebral hemorrhage

Abstract: The risk factors for the pulmonary infections after hypertensive cerebral hemorrhage remains unclear. We aimed to investigate the potential risk factors for the postoperative pulmonary infection in patients with hypertensive cerebral hemorrhage. Patients with hypertensive cerebral hemorrhage undergone surgery from January 2018 to December 2019 were included. Related personal and medical information were collected. Univariate and multivariate logistic regression analyses were performed to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Its onset mechanism for patients with chronic hypertension or blood pressure significantly causes brain artery lesions and causes blood vessel burst bleeds. A large number of intracranial hematomas occur in patients [ 1 ]. If the diagnosis and treatment are not made in time, the amount of intracranial hematoma will be further aggravated and the life safety of patients will be seriously affected [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its onset mechanism for patients with chronic hypertension or blood pressure significantly causes brain artery lesions and causes blood vessel burst bleeds. A large number of intracranial hematomas occur in patients [ 1 ]. If the diagnosis and treatment are not made in time, the amount of intracranial hematoma will be further aggravated and the life safety of patients will be seriously affected [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This limitation of treatment may lead to a decline in patients' confidence in treatment, irritation, and other negative emotions, thus reducing patients' compliance. It has a negative effect on the overall treatment [ 5 , 6 ]. In the literature, the nursing intervention measures for the prevention of postoperative complications of cerebral hemorrhage are summarized as early monitoring, physical prevention, drug prevention, strengthening management, psychological nursing, and so on, but there is a lack of overall evaluation of patients and no systematic nursing thinking.…”
Section: Introductionmentioning
confidence: 99%
“…This also accounts for the high morbidity and mortality rate of patients with hypertensive cerebral hemorrhage. Previous studies have shown that because hypertensive basal ganglia hemorrhage requires prompt surgical treatment, though the surgical field of conventional craniotomy and craniectomy is clear and can completely evacuate hematoma and promptly lower ICP, the surgery is invasive, has a large volume of blood loss, and patients need a long course of postoperative recovery and have many complications with a poor prognosis ( 12 ). With continuing advances in medical technology, microscopic techniques have been widely used in clinical treatment, and burr hole intracranial hematoma evacuation and minimally invasive burr hole drainage have been promoted clinically.…”
Section: Discussionmentioning
confidence: 99%